Molecular Interactions Between Components of the Circadian Clock and the Immune System. Issue 12 (29th May 2020) - Hergenhan, Sophia; Holtkamp, Stephan; Scheiermann, Christoph
Abstract: The immune system is under control of the circadian clock. Many of the circadian rhythms observed in the immune system originate in direct interactions between components of the circadian clock and components of the immune system. The main means of circadian control over the immune system is by direct control of circadian clock proteins acting as transcription factors driving the expression or repression of immune genes. A second circadian control of immunity lies in the acetylation or methylation of histones to regulate gene transcription or inflammatory proteins. Furthermore, circadian clock proteins can engage in direct physical interactions with components of key inflammatory pathways such as members of the NFκB protein family. This regulation is transcription independent and allows the immune system to also reciprocally exert control over circadian clock function. Thus, the molecular interactions between the circadian clock and the immune system are manifold. We highlight and discuss here the recent findings with respect to the molecular mechanisms that control time-of-day-dependent immunity. This review provides a structured overview focusing on the key circadian clock proteins and discusses their reciprocal interactions with the immune system. Graphical abstract: Image 1 Highlights: The immune system is under control of the circadian clock. Circadian clock proteins act as transcription factors controlling genes of the immune system. Circadian clock proteins engage in direct physical interactions with inflammatory proteins. Immune factors also reciprocally exert control over circadian clock function.